Both cancerous miR‐21 and stromal miR‐21 in urothelial carcinoma are related to tumour progression. Issue 6 (16th September 2016) - Ohno, Rena; Uozaki, Hiroshi; Kikuchi, Yoshinao; Kumagai, Arisa; Aso, Tatsuya; Watanabe, Masato; Watabe, Shiori; Muto, Satoru; Yamaguchi, Raizo
Abstract : Aims: Urothelial carcinoma (UC) is a globally common cancer. miR‐21 appears to be important in the tumorigenesis of almost all types of human cancer. However, its precise localization and significance in UC have yet to be clarified. The aim of this study was to examine miR‐21 expression in UC and reveal its clinicopathological importance. Methods and results: Tissue arrays of 232 UCs were examined for miR‐21 by the use of in‐situ hybridization. One hundred and forty‐eight transurethral resection specimens and 84 surgically resected specimens were used. After miR‐21 positivity had been evaluated separately in tumour cells and the tumour stroma, it was compared with clinicopathological factors and overall survival. miR‐21 was strongly expressed in tumour cells in 9% of cases and in the tumour stroma in 6% of cases. Stromal miR‐21 positivity was lower than that of cancerous miR‐21. Both miR‐21s were correlated with each other and related to tumour stage, locus, and histological grade. In addition, strong positivity of miR‐21 in cancer and the stroma was significantly related to poorer prognosis among surgically resected cases. In a Cox proportional hazard model, cancerous miR‐21 was the only independent prognostic factor except for tumour stage. Conclusions: miR‐21 in both cancer and stromal cells is closely related to tumour progression in UC. miR‐21 may be a prognostic marker for cancer progression.